Exposure to aerosolized staphylococcal enterotoxin B potentiated by lipopolysaccharide modifies lung transcriptomes and results in lung injury in the mouse model. Issue 7 (11th February 2022) - Zong, Fuliang; Gan, Changjiao; Wang, Yifeng; Su, Duo; Deng, Mengyun; Xiao, Nan; Zhang, Zhipeng; Zhou, Dongsheng; Gao, Bo; Yang, Huiying
Abstract: Lipopolysaccharide (LPS) is one of the main constituents of the cell wall in Gram ‐ negative bacteria. Staphylococcal enterotoxin B (SEB) is produced by the Gram ‐ positive opportunistic pathogen, Staphylococcus aureus . Emerging evidence suggests that intraperitoneal injection of LPS combined with low‐dose aerosolized SEB exposure can cause severe lung injury and even death, while SEB or LPS alone cause neither mortality nor severe pulmonary symptoms in mice. However, pulmonary effects from exposure to aerosolized SEB potentiated by LPS have not been evaluated. This study investigates the global transcriptome profile of lung tissue in mice after exposure to aerosolized SEB potentiated by LPS or LPS alone. A mouse model of intratracheal exposure to LPS‐potentiated aerosolized SEB is established and described through histological examination. Transcriptome analysis revealed LPS‐potentiated aerosolized SEB affected mouse lungs within 72 h post‐SEB inhalation, gradually causing lung injury starting from 24 h post inhalation. Hub genes leading to lung injury at 48 h post inhalation have been identified. Flow cytometry revealed that LPS potentiation of low‐dose SEB produces a superantigen response that T cells expressing a particular T cell receptor Vβ induces a proliferation response by 72 h post inhalation in the lungs of mice. This study represents the first research to investigate pulmonary transcriptional responses of LPS‐potentiated aerosolized low‐dose SEB exposure. This research helps to elucidate the molecular mechanisms underlying the process by which the two bacterial components combined to produce lung damage and provides an insight into potential treatments for alleviating inflammation of the lung when coinfection is present. Abstract : Animal response to infections involves dynamic changes in gene expression. We have described the global transcriptome profile of lung tissue in mice after exposure to aerosolized staphylococcal enterotoxin B (SEB) potentiated by lipopolysaccharide (LPS). Using a variety of bioinformatic techniques and flow cytometry, we confirmed that low‐dose SEB acts as a superantigen when potentiated by LPS and can activate Vβ T lymphocytes. This study elucidated the mechanism by which the combined action of the two bacterial components triggers lung injury.